Internal control system improvement on ukrainian dairy industry enterprises - Krivobok, Pavlo (My University, 2014)
Nowadays dairy industry holds one of the leading positions in the food industry of Ukraine.
Keywords: competitiveness of the dairy industry; internal control of the enterprise; внутрішній контроль підприємства; конкурентоспроможність молочної промисловості